Determinant Kinerja Karyawan: Analisis Gaya Kepemimpinan dan Kepuasan Kerja pada Industri Pangan di Tangerang Selatan: Employee Performance Determinants: Analysis of Leadership Style and Job Satisfaction in the Food Industry in South Tangerang - Aditya Anarini Ramdhani (PT Cakrawarti Empat Proksi, 2026)
PT Sinergi Pangan Gemilang, South Tangerang, is a food distribution company that requires optimal employee performance to face intense business competition. This study aims to analyze the influence of leadership style and job satisfaction on employee performance at PT Sinergi Pangan Gemilang, South Tangerang. The study used a quantitative method with saturated sampling, resulting in a sample size of the entire population of 30 employees. Data collection was conducted through questionnaires using a Likert scale. Based on the results, the leadership style variable (X1) did not have a positive and significant effect on employee performance (Y), with a calculated t-value of 1.738 < t-table 2.052 and a significance level of 0.094 > 0.05. The job satisfaction variable (X2) has a positive and significant effect on employee performance (Y), as indicated by t count > t table (2.701 > 2.052) with a significance level of 0.012 < 0.05. Simultaneously, leadership style (X1) and job satisfaction (X2) significantly influence employee performance, with an F count of 49.515 and an F table of 3.354 at a significance level of 0.001 < 0.05. The coefficient of determination (R²) of 78.6% indicates that leadership style and job satisfaction jointly influence employee performance, while the remaining influence is attributed to other variables not examined.